Anticipatory cash transfers for climate resilience: Findings from a randomized experiment in northeast Nigeria - Balana, Bedru; Adeyanju, Dolapo; Clingain, Clare; Andam, Kwaw S.; de Brauw, Alan; Yohanna, Ishaku; Olarewaju, Olukunbi; Schneider, Molly (International Food Policy Research Institute, 2023)
This paper presents the findings from an experimental study designed to assess the impacts of one-off large lump sum cash transfers on food security, climate adaptive actions, and climate resilience of smallholders in climate-risk and conflict-affected communities in northeast Nigeria. This pilot intervention was supported by Google.org and implemented by the International Rescue Committee (IRC) in collaboration with the international Food Policy Research Institute (IFPRI). The central hypothesis of the intervention was that when climate vulnerable communities have timely access to information and the financial and social resources to act upon that information, they will avoid negative coping strategies and build more diversified and climate resilient livelihoods. A one-off lump sum of anticipatory cash was transferred to a randomly sampled treatment households in flood-prone areas in northeast Nigeria when triggered by the climate data risk thresholds. Comparable households in a control group received an equal amount of cash post-flooding shock. The main purpose of the study was to assess the impacts of anticipatory cash against the traditional humanitarian post-shocks supporting mechanism. We collected baseline and endline data from a sample of 1450 experimental households (725 ‘treatment’ and 725 ‘control’) and analyzed the data using econometric models. Several outcome indicators including food security, climate adaptive and resilience actions, and wellbeing measures were used to assess the intervention. The results indicate that anticipatory cash has significant impacts on increasing the number of pre-emptive climate adaptive actions and enhancing future resilience to climate shocks. On other hand, anticipatory cash transfers do not seem to have significant impacts on short-term food and non-food consumption expenditures compared to post-shock cash transfers. Our findings indicate that one-off large sum anticipatory transfer could lead households to build their climate resilience capacity, and hence a promising intervention to reduce the vulnerability of households to future climate shocks. Based on the findings we have two key recommendations: (1) Given the generally positive findings on household’s climate adaptive and climate resilience capacity, we suggest humanitarian agencies and governments to consider anticipatory interventions such as anticipatory cash transfers as a mechanism for both meeting basic needs and improving climate resilience of households if quality data and analytics exist to predict a high probability of climate shocks. (2) As climate shocks continue to worsen and humanitarian funding needs remain unmet for both emergencies and early recovery, anticipatory approach may be critical to meeting the short- and long-term needs of climate- and conflict-affected households.